2019
DOI: 10.3201/eid2507.180491
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Associated Multicenter Outbreak of Emerging Fungus Candida auris, Colombia, 2016

Abstract: Adherence to infection control recommendations is critical to prevent spread of this novel yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 19 publications
3
62
0
6
Order By: Relevance
“…Reliance on traditional methods may lead to misidentification. Candida auris is usually resistant to fluconazole [4] and has been associated with resistance to multiple antifungal drug classes including echinocandins and amphotericin B [5]. The case fatality of bloodstream infections with C. auris has been reported to be up to 60% and the infections may be difficult to treat because of resistance to multiple antifungal agents [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…Reliance on traditional methods may lead to misidentification. Candida auris is usually resistant to fluconazole [4] and has been associated with resistance to multiple antifungal drug classes including echinocandins and amphotericin B [5]. The case fatality of bloodstream infections with C. auris has been reported to be up to 60% and the infections may be difficult to treat because of resistance to multiple antifungal agents [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, Candida auris has emerged in healthcare settings as a multidrug-resistant organism in over 30 countries worldwide (1). Primarily a skin colonizer, this pathogenic yeast can cause bloodstream infections and other infections (2), is often resistant to multiple classes of antifungal drugs (3, 4), and can spread via nosocomial transmission causing outbreaks of invasive infections (512).…”
Section: Introductionmentioning
confidence: 99%
“…An important objective of this EQA was to raise awareness about the potential misidentification of C. auris and its ability to cause nosocomial outbreaks, as early recognition is pivotal to limit the unrecognized spread of C. auris in the hospital environment [3,9,31,32]. As similar to the results of a laboratory survey in Belgium that was conducted during the same period, the results of this EQA indicated that not all laboratories were aware of the potential risks of C. auris, nor of the limitations of their yeast identification protocols [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another study used the Bruker MALDI Biotyper to identify isolates belonging to the African clade III [46]. Isolates form the South American clade IV were reported to be correctly identified with the Bruker MALDI Biotyper [3,47]. However, as it was not the objective to evaluate the performance of the MALDI-TOF MS during the latter three studies, no reference methods for the identification were used, and it is not known how many isolates were misidentified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation